2016
DOI: 10.1007/s11248-016-9958-0
|View full text |Cite
|
Sign up to set email alerts
|

Silencing porcine genes significantly reduces human-anti-pig cytotoxicity profiles: an alternative to direct complement regulation

Abstract: Silencing the GGTA1, CMAH and B4GalNT2 genes in pigs achieved a significant antigen reduction. Changing the porcine carbohydrate profile effectively mediates human antibody-mediated complement dependent cytoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…We have also previously reported that fully allogeneic porcine VTL grafts in recipients treated with 28 days of tacrolimus facilitated induction of tolerance of VTL‐matched kidneys that were transplanted 3 months after VTL grafts without immunosuppression in a swine model . We will now combine these delayed XLTx strategies with a tolerance‐inducing preconditioning regimen which includes lung‐specific treatments, as well as utilizing new TGs donors to determine whether they will overcome the unique immunologic barriers in XLTx.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We have also previously reported that fully allogeneic porcine VTL grafts in recipients treated with 28 days of tacrolimus facilitated induction of tolerance of VTL‐matched kidneys that were transplanted 3 months after VTL grafts without immunosuppression in a swine model . We will now combine these delayed XLTx strategies with a tolerance‐inducing preconditioning regimen which includes lung‐specific treatments, as well as utilizing new TGs donors to determine whether they will overcome the unique immunologic barriers in XLTx.…”
Section: Resultsmentioning
confidence: 98%
“…It is therefore clear that further strategies will be required to prolong lung graft survival from days to months. To protect the alveolar capillary network, in addition to adding hCD47 and other vascular protective genes as well as genes to reduce antigens against non‐Gal Abs, strategies to minimize inflammatory responses caused by pre‐formed Nab, macrophages, NK cells, T cells, and B cells must be considered prior to XLTx. We are currently exploring delayed lung transplantation in recipients that have received tolerance‐inducing preconditioning with lung‐specific strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of B4GALNT2 in human cells significantly increased antibodydependent complement-mediated lysis when these cells were challenged with serum from pig-to-baboon cardiac xenotransplantation sensitized recipient serum [25] while its deletion in pig PBMCs efficiently reduced human IgG and IgM binding and decreased human anti-porcine cytotoxicity [26,27]. The fact that a strong humoral response was detected in nonhuman primates receiving alginate-encapsulated islets especially against αGal [28,29] further emphasizes the necessity to use GGTA1-KO pigs as a background for other genetic modifications.…”
Section: Modification Of Donor Pigs To Mitigate the Immunementioning
confidence: 99%
“…Today, research groups can produce multiple gene knock-out or knock-in pigs using CRISPR technology [8794], which can also be used to delete PERV expression [74,95]. Genetically-modified pigs using CRIPSR technology have been used in several important studies relating to antibody binding [9698] and coagulation dysfunction [99,100]. There are now more than 26 genetically-engineered pigs for xenotransplantation research (Table 2).…”
Section: Introductionmentioning
confidence: 99%